NAFLD or MAFLD: Which Has Closer Association With All-Cause and Cause-Specific Mortality?—Results From NHANES III - Huang, Qi; Zou, Xiantong; Wen, Xin; Zhou, Xianghai; Ji, Linong (Frontiers in Medicine, 2021)
Background The recent change of terminology from non-alcoholic fatty liver disease (NAFLD) to metabolic dysfunction-associated fatty liver disease (MAFLD) has raised heated discussion. We aim to investigate the association of MAFLD or NAFLD with all-cause and cause-specific mortality to compare the outcomes of the two diagnostic criteria in population-based study. Methods We recruited 12,480 participants from the Third National Health and Nutrition Examination Survey (NHANES III) with matched mortality data in 2015. Participants were divided into four groups for survival analysis: without NAFLD or MAFLD, with only NAFLD, only MAFLD. Cox proportional hazard regression was used to estimate multivariable-adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for all-cause and cause-specific mortality. Subgroup analysis were applied in MAFLD patients. Results The weighted prevalence of MAFLD and NAFLD was relatively 27.4% and 27.9%. Participants with NAFLD or MAFLD were largely overlapped (weighted Cohen’s kappa coefficient 0.76). MAFLD increased the overall risk for total mortality in a greater magnitude than NAFLD (HR 2.07 [95% CI 1.86, 2.29] v.s. 1.47 [1.20, 1.79]), However, the difference was non-significant after metabolic parameters were adjusted. Risks for cardiovascular, neoplasm, and diabetes-related mortality were similar between MAFLD and NAFLD. Referring to individuals without both NAFLD and MAFLD, individuals with only NAFLD showed reduced total mortality (HR 0.48 [0.34,0.68]) and neoplasm mortality (HR 0.46 [0.24,0.89]) in crude. Nevertheless, individuals with only MAFLD independently increased the risk for total mortality (adjusted HR 1.47 [1.22, 1.77]) and neoplasm mortality (aHR 1.58 [1.09, 2.28]). The risk for overall mortality in MAFLD was consistent between subgroups except for race-ethnicity and whether secondary to viral hepatitis. Conclusions Participants with MAFLD or NAFLD were highly concordant. MAFLD showed greater risk for all-cause mortality and equal risk for cause-specific mortality referring to NAFLD. The new terminology excluded participants with lower mortality risk and included participants with higher risk. Drug development for MAFLD should consider ethnic differences.